Revision and cladistic analysis of the Guineo-Congolian spider genus Smeringopina Kraus (Araneae, Pholcidae) - Huber, Bernhard A. (Zootaxa, 2013)
The genus Smeringopina Kraus, 1957 is revised, with redescriptions of the nine previously known species and descriptions of 35 new species. Smeringopina is largely restricted to the tropical forests of West and Central Africa. It includes both large species that build their domed sheet-webs in protected spaces near the ground, and small (probably derived) litter-dwelling species. With leg spans up to 18 cm the former group includes some of the largest pholcids known. A first cladistic analysis of Smeringopina, based on 68 morphological (including SEM) characters, suggests several well-defined species groups but also identifies some problematic species whose phylogenetic position needs further study. The ‘Dahomey-Gap’ separates two small western clades (the guineensis species group and two species of the ankasa group) from all other species. The following new species are described: S. ankasa; S. attuleh; S. bamenda; S. bayaka; S. belinga; S. bioko; S. bomfobiri; S. bwiti; S. chaillu; S. djidji; S. ebolowa; S. essotah; S. etome; S. fang; S. fon; S. ibadan; S. iboga; S. kala; S. kikongo; S. kinguele; S. kribi; S. lekoni; S. luki; S. mayebout; S. mbouda; S. mohoba; S. moudouma; S. ndjole; S. ngungu; S. nyasoso; S. ogooue; S. sahoue; S. simintang; S. tchimbele; S. tebe.